EKSPLORASI VARIASI SUMBERDAYA PARIWISATA LOKAL UNTUK BERTAHAN DARI SERANGAN PANDEMI COVID-19 - Prabowo, Agung; Dwi Abadi, Medi Trilaksono; Utami, Yenni Sri (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Information and communication technology has consistently changed the culture and way of seeing people in traveling. Tourism activities that were previously only a complementary priority are now turning into a top priority for the community. The high interest in traveling stimulates the creativity of various groups of people to explore the potential of their area to become a tourist destination. Geographical, culinary, handicraft and cultural potentials are growing in various regions. Pasar Setu Minggu (Semi) Kaki Langit is one of the tourist destinations developed by the Mangunan community by exploring regional potential and traditional culinary wealth. The development is quite good and able to lift the people’s economy. However, after Covid-19 occurred, for four months there were no visits at all. Market facilities that have no activity have become a little neglected. However, after signs of community tourism activity improved, residents were excited to improve tourist facilities based on Covid-19. The change in the concept of tourism based on Covid-19 certainly needs to be communicated to consumers. Information and communication technology and delivering interesting content are expected to be able to accelerate the recovery of Kaki Langit tourism. This community service aims to help restore Kaki Langit tourist destinations through packaging of local products.